A recente produção científica sobre currículo e multiculturalismo no Brasil (1995-2000): avanços, desafios e tensões - Antônio Flávio Moreira Barbosa (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2001)
This article presents an analysis of recent Brazilian scientific production on curriculum and multiculturalism. It examines articles published between 1995 and 2000 in the following journals: Cadernos de Pesquisa, Revista Brasileira de Educação, Educação & Realidade, Educação & Sociedade e Educação em Revista. It also focuses on papers presented at the Annual Meetings of ANPEd during the same period. The study aims at identifying the main themes and arguments, the most significant theoretical influences, the methodological procedures employed, the contributions and the gaps. The tensions and challenges observed in the articles are also discussed. The paper insists on the importance of a dialogue between those authors more closely associated with social movements who are chiefly influenced by social theory and anthropology and those authors more closely associated with curriculum and pedagogy who are influenced by critical theory, cultural studies, post-modernism and post-structuralism.